The Effect of Preconception Nutritional Status on Birth Weight of Babies in Maternity Women in Purwakarta Regency, Indonesia - Purnamawati, Leli (HM Publisher, 2024)
Preconception nutritional status is one of the factors that can influence a baby's birth weight. This study aims to determine the effect of preconception nutritional status on birth weight of babies in maternity mothers in Purwakarta Regency, Indonesia. This research uses a descriptive analytical research design with a cross-sectional approach. The research sample was 100 maternity mothers in Purwakarta Regency, Indonesia. Data was collected through interviews and anthropometric examination. Data analysis used the Pearson correlation test. The results of the study showed that there was a significant relationship between preconception nutritional status and the baby's birth weight (r=0.714; p<0.001). Mothers with good preconception nutritional status have a lower risk of giving birth to babies with low birth weight (LBW) compared to mothers with poor or poor preconception nutritional status. The conclusion of this study is that preconception nutritional status has a positive effect on the baby's birth weight. Therefore, it is important for women of childbearing age to maintain their nutritional status so they can give birth to healthy and prosperous babies.